A cat story - Husted, Ursula Murray (Quill Tree Books/Harper Alley, 2020)
"Cilla and Betto are two friends who need a place to call home. The docks in Valletta are too wet, and the scraps of food too scarce. The city's streets are too busy, and the humans too unreliable. But what about the quiet garden from old kitten tales--a place where all cats are welcome, and the humans are always kind? Could the stories really be true? As Cilla and Betto embark on a grand adventure to find out, they begin to spin a tale of their own--one that will take them through the art and stories of many journeyers who came before, and that will bring them to a surprising destination."--Provided by publisher